2017
DOI: 10.1186/s12880-017-0199-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pediatric and adult CT organ dose estimation methods

Abstract: BackgroundComputed Tomography (CT) contributes up to 50% of the medical exposure to the United States population. Children are considered to be at higher risk of developing radiation-induced tumors due to the young age of exposure and increased tissue radiosensitivity. Organ dose estimation is essential for pediatric and adult patient cancer risk assessment. The objective of this study is to validate the VirtualDose software in comparison to currently available software and methods for pediatric and adult CT o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…For the bone marrow, CT-Expo estimated a dose much higher than those estimated by the other three software applications. This is because the phantom implemented in CT-Expo does not have a specific representation for the bone marrow and the bone surface, but it applies a correction factor to the dose received from the entire bone structure [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the bone marrow, CT-Expo estimated a dose much higher than those estimated by the other three software applications. This is because the phantom implemented in CT-Expo does not have a specific representation for the bone marrow and the bone surface, but it applies a correction factor to the dose received from the entire bone structure [36].…”
Section: Discussionmentioning
confidence: 99%
“…For these organs, the scattering contribution becomes important and a statistical error has to be taken into account, due to the Monte Carlo calculation uncertainties which increase while reducing the number of photons [45]. A difference of a few millimetres in the scan extent can change the dose result by some factors [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomy selection and accurate representation of patient size and composition are important considerations for pediatric CT patients, because organ dose changes are relatively greater in smaller patients depending on anatomy selection. A recent study demonstrated organ dose change resulting from inclusion or exclusion of an organ in scan range is more drastic in small patients [34]. In light of the wide range of considerations for accurate dosimetry, including patient size, age and imaging technique, a variety of dosimetry methodologies including those examined in the current study are beneficial to have on hand.…”
Section: Discussionmentioning
confidence: 99%
“…The k-factors based on voxel phantoms should be more applicable to CT patients compared with the conversion factors calculated from stylized phantoms, especially for the organs with high tissue weighting factors such as the breast, bone marrow, colon, lungs, and stomach. Effective dose estimated from stylized phantoms is reported to be different from realistic voxel phantoms by up to 40% (for head/ neck and abdomen-pelvis scans) [9]. Lastly, k-factors from phantoms with reference size may under-or overestimate actual effective dose delivered to underweight and overweight patients, respectively [10].…”
mentioning
confidence: 99%